PHRASE THEORY. PHRASE TYPES AND SUBTYPES CORDINATE AND SUBORDINATE AND PREDICATIVE PHRASES ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article provides a detailed exploration of phrase theory, focusing on the various types of phrases—coordinate, subordinate, and predicative—and their subtypes. It begins with a general introduction to the concept of phrases in linguistics, explaining their role as groups of words that function together within a sentence. The article then delves into each type of phrase, providing definitions, examples, and an explanation of how they interact with other elements of sentence structure.  Coordinate phrases are explained as syntactic units consisting of equal elements connected by conjunctions. Subordinate phrases are described as dependent structures that cannot stand alone and are introduced by subordinating conjunctions. Finally, predicative phrases are highlighted as essential for linking the subject to a complement, typically following a linking verb. The article emphasizes the importance of understanding phrase theory for constructing grammatically correct sentences and enhancing language comprehension. It concludes by reaffirming that a deep understanding of phrase types enriches both the analysis and use of language. This resource is beneficial for linguistics students, language learners, and anyone seeking to deepen their understanding of sentence structure and syntax.